Distribution of Holstein Friesian Dairy Cattle Populations in KUD Gemah Ripah Sukabumi, West Java for Milk Production of during Lactation, Daily Milk Production, and Fat Levels - Raden Febrianto Christi; H. Hermawan; Lia Budimulyati Salman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
Dairy cows are a type of livestock that have been developed by contributing products in the form of milk as a provider of animal protein. The more dairy cow population, the higher the milk production produced. This study aims to determine the population of dairy farming in Gemah Ripah Sukabumi KUD, West Java, and to determine the amount of milk production during the lactation period, daily milk production, and fat content. The research method used was a survey by taking primary and secondary data in 2018 and then analyzed with simple statistics to determine the mean, standard deviation, and coefficient of diversity. The results showed that the population of dairy cows was widespread in the Sukabumi area. Namely in the Barokah group in the Sukalarang sub-district, the Cikole group in the Sukaraja sub-district, the Cintaresmi group in the Sukalarang sub-district, the Priangan group in the Sukalarang sub-district, the rukun tani II in the sub-district of Sukalarang, the rukun tani III in Sukalja, sulanjana I in Sukalarang sub-district. Sukalarang sub-district, sulanjana II sub-group sukalarang sub-district, sukalarang talisaid sub-district, Darma Sancang group, Sukaraja group consisting of calves, young dairy cows, dairy cows, and bulls with average total milk production (362.7) 3627 liters/lactation, average the amount of daily milk production is 10.8 liters/head/day. The average fat content is 3.44%. The conclusion showed that the population of dairy cows that was in Gemah Ripah Cooperative Sukabumi District has a total of 776 heads. Consisting of calves, heifers, cow lactation, and males as well as having an average total milk production during the lactation period with 105 heads, which is 362.5 liters/lactation, the average daily milk production of 10.8 liters/head/day, with a fat content of 3.44%.